Employee Performance in Hybrid Work: The Role of Virtual Training and Job Autonomy - Sunarto Sunarto; Butet Sinaga; Muhammad Umar (Goodwood Publishing, 2025)
Purpose: This study examines the effects of Virtual Training, Job Autonomy, Employee Engagement, Innovation Culture, and Work Well-being on Employee Performance in hybrid work settings in Indonesia. Research Methodology: This research adopts a quantitative explanatory design using a cross-sectional survey of 150 hybrid employees across multiple industries. Data were analyzed using Partial Least Squares structural equation modeling (PLS-SEM) with SmartPLS 4.0 to test the structural relationships among variables. Results: The findings revealed that only Innovation Culture had a significant effect on Employee Performance, but in a negative direction (? = ?0.204; p = 0.009). Virtual Training, Job Autonomy, Employee Engagement, and Work Well-being do not show direct significant effects. The model explains 6.5% of the variance in Employee Performance, indicating weak direct explanatory power and suggesting the presence of indirect or contextual influences. Conclusions: Employee performance in hybrid work is influenced more by dynamic organizational contexts than by the direct effects of training, autonomy, engagement, or well-being. Innovation culture may temporarily reduce short-term performance owing to adjustment and experimentation demands. Limitations: This study had a cross-sectional design, relied on self-reported data, and focused on the Indonesian context, limiting causal interpretation and generalizability. Contributions: This study extends the Job Demands–resources framework by revealing the nonlinear role of innovation culture in hybrid work and provides empirical evidence from an emerging economy context.